2010
DOI: 10.1007/s10482-010-9508-3
|View full text |Cite
|
Sign up to set email alerts
|

Past, present and future research directions with Pichia anomala

Abstract: The first International Pichia anomala Symposium provided a survey of past, recent and ongoing research on this yeast. The research community working with this yeast has focussed on several areas. Based on molecular data, a revision of the taxonomy is required: the name P. anomala is no longer applicable, as the genus Pichia is polyphyletic. The current debate centres on whether the yeast should be designated as Wickerhamomyces anomalus or if the previous name, Hansenula anomala, should be re-instated. The ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 34 publications
1
31
0
4
Order By: Relevance
“…These results demonstrate the biocontrol potential of these killer strains on spoilage yeasts, noting that P. guilliermondii Cd6 is an autochthonous strain from northwestern region of Argentina as Cf8 and Cf20 strains. These findings are in concordance with the literature, which express that killer toxins from S. cerevisiae have narrow inhibition spectra, while those belonging from W. anomalus often present broad inhibition spectra [8][9][10].…”
Section: Inhibitory Effect On Wine Spoilage Yeastssupporting
confidence: 92%
“…These results demonstrate the biocontrol potential of these killer strains on spoilage yeasts, noting that P. guilliermondii Cd6 is an autochthonous strain from northwestern region of Argentina as Cf8 and Cf20 strains. These findings are in concordance with the literature, which express that killer toxins from S. cerevisiae have narrow inhibition spectra, while those belonging from W. anomalus often present broad inhibition spectra [8][9][10].…”
Section: Inhibitory Effect On Wine Spoilage Yeastssupporting
confidence: 92%
“…The name Pichia anomala, used in recent years, does not reflect the phylogeny of this species. A new species name, Wickerhamomyces anomalus, has been proposed [9, 10], but some argue to reinstate the former name, H. anomala [20].) Interestingly, we recently found that H. anomala strongly inhibited E. coli and P. agglomerans in cereal grain (14).…”
mentioning
confidence: 99%
“…4) indican que, en las condiciones de crecimiento, no hubo generación de ningún producto carbonado diferente a la biomasa y CO2. Según fue informado por otros autores, P. anomala (W. anomalus) es producida de manera eficiente considerando que es una levadura que presenta efecto Crabtree negativo, es decir que respira y produce biomasa en presencia de O2, independientemente de la concentración de azúcar presente en el medio (Passoth et al, 2011).…”
Section: Resultados Y Discusiónunclassified
“…Una levadura pectinolítica fue aislada a partir de cásca-ras de frutas cítricas en la Provincia de Misiones, Argentina, la cual fue identificada como Wickerhamomyces anomalus, reclasificación de la especie Pichia anomala (Passoth et al, 2011). W. anomalus, al crecer en un medio de cultivo compuesto por Base Nitrogenada para Levaduras (Yeast Nitrogen Base, YNB), glucosa como fuente de carbono y energía (FCE) y pectina de citrus como inductor, excreta al medio una enzima con actividad poligalacturonasa (endo-PG, EC 3.2.1.15).…”
Section: Introductionunclassified